Novel Emblica officinalis extract containing β-glucogallin vs. metformin: a randomized, open-label, comparative efficacy study in newly diagnosed type 2 diabetes mellitus patients with dyslipidemia. Issue 18 (23rd August 2022) - Majeed, Muhammed; Mundkur, Lakshmi; Paulose, Shaji; Nagabhushanam, Kalyanam
Abstract : Comparative clinical trial shows higher efficacy of EOE containing β-glucogallin over metformin in newly diagnosed T2DM patients with dyslipidemia. Abstract : The efficacy of Emblica officinalis extract (EOE) containing 10% β-glucogallin was compared against metformin in newly diagnosed subjects with diabetic dyslipidemia which is a significant factor in cardiovascular disease. Daily administration with EOE-1 g, EOE-2 g, or metformin 500 mg for 90 days significantly decreased fasting blood sugar and postprandial blood sugar (FBS and PPBS), hemoglobin A1c (HbA1c) and lipid levels in all three treatment groups. The FBS, PPBS and HbA1c were significantly lower in the EOE-2 g group compared with metformin and EOE-1 g groups. The reductions in LDL and TC in the EOE-2 g group were also significantly higher than in the EOE-1 g group and were comparable to the metformin group. No serious adverse effects were observed in any study participants. EOE-1 g and 2 g day −1 are safe and potent antidiabetic agents, with comparable efficacy to the pharmaceutical drug, metformin. Supplementation with EOE-2 g day −1 showed greater efficacy than metformin in reducing circulating glucose levels.